DENSITAS BULU BABI (Echinoidea) PADA PERAIRAN PANTAI NAPABALANO KECAMATAN NAPABALANO KABUPATEN MUNA - , La Hafini, S.Pd. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Sea urchin (Echinoidea) is a kind of invertebrate which is often found in tidal zones with stony fine sand, coral reefs and sandy rocks. Sea urchin has a very important role in the ecology of coral reef, especially in tidal zones. The purpose of this research was to determine the density of sea urchin in Napabalano Coastal, Napabalano, Muna, Southeast Sulawesi. The sampling was conducted at four stations, that are Latawe Coastal, Lakura Coastal, Tampo Coastal and Lambiku Coastal. The determination of the location was conducted by purposive sampling. The research method was conducted by transec line. The results showed that there were four species of sea urchins, that is Diadema setosum, Diadema sp., Echinotrix calamaris and Tripneustes gratilla. The density of Diadema setosum was the highest with 0,464 ind./m 2 in the rocky habitat of fine sand and coral reefs. The density of Diadema sp. was 0,322 ind./m 2 in sand rocky reef habitat and there is no smooth rocky sand. Echinotrix calamaris was found only in coral reef with 0,145 ind./m 2 density. Tripneustes gratilla was found in seagrass and algae coral reef with 0,043 ind./m2 density. The results of correlation analysis of water quality and substrate with the density of sea urchin showed that the TDS has a positive correlation with the density of sea urchin. The increase of TDS, affect the increase of the density of sea urchin. In contrast, NH3 and N-total have a negative correlation with the density of sea urchin. The increase of NH3 and N-total, affect the decrease of the density of sea urchin.